2018
DOI: 10.17576/gema-2018-1803-08
|View full text |Cite
|
Sign up to set email alerts
|

Spoken Metadiscourse in Malaysian ESL Job Interviews

Abstract: Various job interview skills training have been carried out to prepare students for employment. However, the outcome of job interviews is questionable, as one of the reasons for unemployment among Malaysian graduates is their inability to communicate competently in job interviews. The Malaysia Education Blueprint 2015-2025 (Higher Education) stated that unemployed graduates were also lacking in a strong command of English. Since job interviews are placed heavily on verbal exchanges between the interviewer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…When these results are compared to those of previous research on metadiscourse, one can see that there are points of similarities and points of differences. Previous research indicated that interactive markers are used more in written discourses (Hyland & Tse, 2004& Khedri, 2014, whereas interactional markers are used more in spoken discourses (Cavalieri, 2011;Adel, 2012;Yipei & Lingling, 2013;Malmstrom, 2014;Lee & Subtirelu, 2015;Turiman et al, 2018;Mahmood & Kasim, 2019;Mahmood & Kasim, 2021). Even though the texts analyzed in this study are written, interactional markers are used more than interactive markers which can be attributed to the difference in the type of texts and genre (Adel, 2012, p. 93).…”
Section: Above)mentioning
confidence: 64%
“…When these results are compared to those of previous research on metadiscourse, one can see that there are points of similarities and points of differences. Previous research indicated that interactive markers are used more in written discourses (Hyland & Tse, 2004& Khedri, 2014, whereas interactional markers are used more in spoken discourses (Cavalieri, 2011;Adel, 2012;Yipei & Lingling, 2013;Malmstrom, 2014;Lee & Subtirelu, 2015;Turiman et al, 2018;Mahmood & Kasim, 2019;Mahmood & Kasim, 2021). Even though the texts analyzed in this study are written, interactional markers are used more than interactive markers which can be attributed to the difference in the type of texts and genre (Adel, 2012, p. 93).…”
Section: Above)mentioning
confidence: 64%
“…Based on extensive literature search, we found that studies on English language acquisition in the Malaysian context have been mainly carried out on Malaysian tertiary learners and graduates (e.g. Isai et al 2020;Mohd Zin, Eng, and Rafik-Galea 2014;Sarudin et al 2013;Ting et al 2017;Turiman, Abdullah, and Mohd Noor 2018;Zainuddin et al 2018). We posit that to understand the underlying cause of Malaysian learners' English performance, studies investigating learners' development at the earlier level, such as at the preschool levels, are necessary.…”
Section: Preschool and English Language Education In Malaysiamentioning
confidence: 99%
“…Metadiscourse features are also examined in different disciplines and languages, for example Blagojevic (2004) and Dahl (2004). They are also scrutinised in non-academic spoken discourse as in parliamentary debates (Ilie, 2003), in Malaysian ESL job interviews (Turiman et al, 2018); and in non-academic written discourse specifically in fiction genre (AlJazrawi and AlJazrawi, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%